Attenuating anger and aggression with neuromodulation of the vmPFC: A simultaneous tDCS-fMRI study. (December 2018) - Gilam, Gadi; Abend, Rany; Gurevitch, Guy; Erdman, Alon; Baker, Halen; Ben-Zion, Ziv; Hendler, Talma
Abstract: Angry outbursts during interpersonal provocations may lead to violence and prevails in numerous pathological conditions. In the anger-infused Ultimatum Game (aiUG), unfair monetary offers accompanied by written provocations induce anger. Rejection of such offers relates to aggression, whereas acceptance to anger regulation. We previously demonstrated the involvement of the ventro-medial prefrontal cortex (vmPFC) in accepting unfair offers and attenuating anger during an aiUG, suggestive of its role in anger regulation. Here, we aimed to enhance anger regulation by facilitating vmPFC activity during anger induction, using anodal transcranial direct current stimulation (tDCS) and simultaneously with functional Magnetic Resonance Imaging to validate modulation of vmPFC activity. In a cross-over, sham-controlled, double-blind study, participants (N = 25) were each scanned twice, counterbalancing sham and active tDCS applied during administration of the aiUG. Outcome measures included the effect of active versus sham stimulation on vmPFC activity, unfair offers' acceptance rates, self-reported anger, and aggressive behavior in a subsequent reactive aggression paradigm. Results indicate that active stimulation led to increased vmPFC activity during the processing of unfair offers, increased acceptance rates of these offers, and mitigated the increase in self-reported anger following the aiUG. We also noted a decrease in subsequent aggressive behavior following active stimulation, but only when active stimulation was conducted in the first experimental session. Finally, an exploratory finding indicated that participants with a stronger habitual tendency to use suppression as an emotion regulation strategy, reported less anger following the aiUG in the active compared to sham stimulation conditions. Findings support a potential causal link between vmPFC functionality and the experience and expression of anger, supporting vmPFC's role in anger regulation, and providing a promising avenue for reducing angry and aggressive outbursts during interpersonal provocations in various psychiatric and medical conditions.